Dynamic heat transfer mechanisms of internal thermal mass: Effects of thermal conductivity and diffusivity under varied temperature conditions - Ru Yang; Liting Yuan; Dong Zhang; Taiquan Wu; Yihang Lu (Case Studies in Thermal Engineering)
The appropriate use of internal thermal mass in buildings can reduce energy consumption while maintaining thermal comfort. A prerequisite for selecting suitable internal thermal mass is to establish its relationship with indoor air temperature and heat exchange. However, there is currently a lack of analytical models to describe this relationship. This study investigates the dynamic heat transfer performance of internal thermal mass under constant indoor air temperature, exponentially declining temperatures, and sinusoidal heating and cooling conditions. The results show that under constant indoor air temperature, materials with lower thermal conductivity (e.g., plywood with 0.17 W/m·°C) generate more thermal waves and experience faster surface temperature rises compared to materials with higher conductivity (e.g., reinforced concrete with 1.74 W/m·°C). In the case of exponentially declining indoor air temperature, heat exchange per unit area decreases with increasing thickness, with plywood (0.02 m) reaching its peak temperature at 6360 s, and reinforced concrete (0.2 m) at 9900 s. For sinusoidal temperature variations, the decrement factor for plywood and reinforced concrete decreases from 0.90 to 0.59 as thickness increases from 0.02 m to 0.06 m, while the time lag increases from 1.45 h to 3.16 h. The heat exchange is primarily related to the effective thermal capacity per unit area and the storage coefficient, which are determined by the physical properties of the internal thermal mass. These findings provide a quantitative basis for estimating the impact of internal thermal mass on indoor air temperature and heat exchange in the early stages of building design.